Ar-Ar ages, Sr-Nd isotope geochemistry, and implications for the origin of the silicate rocks of the Jacupiranga ultramafic-alkaline complex (Brazil). (August 2017) - Chmyz, Luanna; Arnaud, Nicolas; Biondi, João Carlos; Azzone, Rogério Guitarrari; Bosch, Delphine; Ruberti, Excelso
Abstract: The Jacupiranga Complex is one of several Meso-Cenozoic alkaline intrusive complexes along the margins of the intracratonic Paraná Basin in southern Brazil. The complex encompasses a wide range of rock-types, including dunites, wehrlites, clinopyroxenites, melteigites-ijolites, feldspar-bearing rocks (diorites, syenites, and monzonites), lamprophyres and apatite-rich carbonatites. While carbonatites have been extensively investigated over the last decades, little attention has been paid to the silicate rocks. This study presents new geochonological and geochemical data on the Jacupiranga Complex, with particular emphasis on the silicate lithotypes. 40 Ar/ 39 Ar ages for different lithotypes range from 133.7 ± 0.5 Ma to 131.4 ± 0.5 Ma, while monzonite zircon analyzed by SHRIMP yields a U-Pb concordia age of 134.9 ± 1.3 Ma. These ages indicate a narrow time frame for the Jacupiranga Complex emplacement, contemporaneous with the Paraná Magmatic Province. Most of the Jacupiranga rocks are SiO2 -undersaturated, except for a quartz-normative monzonite. Based on geochemical compositions, the Jacupiranga silicate lithotypes may be separated into two magma-evolution trends: (1) a strongly silica-undersaturated series, comprising part of the clinopyroxenites and the ijolitic rocks, probably related to nephelinite melts and (2) a mildly silica-undersaturated series, related to basanite parental magmas and comprising the feldspar-bearing rocks, phonolites, lamprophyres, and part of the clinopyroxenites. Dunites and wehrlites are characterized by olivine compositionally restricted to the Fo83-84 interval and concentrations of CaO (0.13–0.54 wt%) and NiO (0.19–0.33 wt%) consistent with derivation by fractional crystallization, although it is not clear whether these rocks belong to the nephelinite or basanite series. Lamprophyre dikes within the complex are considered as good representatives of the basanite parental magma. Compositions of calculated melts in equilibrium with diopside cores from clinopyroxenites are quite similar to those of the lamprophyres, suggesting that at least a part of the clinopyroxenites is related to the basanite series. Some feldspar-bearing rocks (i.e. meladiorite and monzonite) show petrographic features and geochemical and isotope compositions indicative of crustal assimilation, although this may be relegated to a local process. Relatively high CaO/Al2 O3 and La/Zr and low Ti/Eu ratios from the lamprophyres and calculated melts in equilibrium with cumulus clinopyroxene point to a lithospheric mantle metasomatized by CO2 -rich fluids, suggesting vein-plus-wall-rock melting mechanisms. The chemical differences among those liquids are thought to reflect both variable contributions of melting resulting from veins and variable clinopyroxene/garnet proportions of the source. Highlights: Two magmatic series are identified for the Jacupiranga silicate rocks. Ar/Ar and U-Pb ages indicate a narrow time frame of emplacement. Lamprophyres are considered as representatives of a basanite parental magma. Local crustal assimilation processes are constrained for some lithotypes. Basanite melts were generated from a mantle source with variable degrees of CO2 -rich metasomatism.